Urgensi Filsafat Ilmu dalam Bimbingan Konseling di Era Digital - Mustika, Humaira; Jamaris, Jamaris; Solfema, Solfema (Jurnal Bimbingan dan Konseling Terapan, 2022)
This study aims to determine the progress of the times accompanied by technological improvements in the digital era. Logical thinking is an important foundation in the development of science, especially in the philosophy of science. The emergence of technology in the digital era has had a major influence on the role of philosophy of science in guidance and counseling in the digital era. Continuation must be the fundamental money to capture, expert, and treat innovation properly and appropriately. The purpose of this research is to find out how far the development of digital era science is in the study of philosophy of science from the perspective of guidance and counseling in the development of the digital era. This research method is qualitative with a literature study approach, or also called a literature review. Literature review is a written summary of articles from journals, documents, and books that explain theories and information that occurred in the past or is currently happening. The results of this study aim to find out how far the development of the digital era is in perspective in the philosophy of science in the context of guidance and counseling in the development of the digital era, and aims to make it easier for counselors to help clients solve their problems by using e-mail media, video conferencing, Facebook and applications in online counseling.